Interictal neural fragility predicts seizure onset zone and surgical outcomes in drug-resistant epilepsy - Yue Pang; Yixuan Yang; Yunqing Lin; Jianyu Zhu; Penghui Liu; Yu Tian; Feng Wang; Zhen Mei; Dezhi Kang; Miao Cao; Yuanxiang Lin (PeerJ)
Epilepsy is a chronic neurological disorder affecting approximately 70 million individuals worldwide, with a significant subset of patients exhibiting drug-resistant epilepsy (DRE). Accurate identification of the seizure onset zone (SOZ) is crucial for successful surgical intervention. This study investigates interictal neural fragility as a potential biomarker for predicting SOZ and guiding treatment outcomes in DRE patients. By applying dynamic mode decomposition (DMD) techniques to interictal stereoelectroencephalography (SEEG) data from 30 patients, we generated patient-specific dynamic network models and constructed fragility heatmaps. Our findings demonstrate that patients with favorable surgical outcomes exhibit significantly higher fragility in the SOZ during interictal periods. The fragility-based SOZ prediction model showed high sensitivity and specificity, with a strong concordance between the predicted SOZ and clinically identified treatment targets. This study highlights the clinical utility of interictal neural fragility in enhancing SOZ localization and improving treatment strategies for patients with low seizure frequency. Future research should focus on integrating this model into clinical workflows and exploring its potential in personalized treatment approaches.